Synthesis and characteristics rubber seed oil bioadditive from Sumatera Utara as low pour point of CPO biodiesel - Misdawati Misdawati; Siswadi Siswadi; Muhammad Said Siregar (Jurnal Pendidikan Kimia, 2024)
One of the drawbacks of Crude Palm Oil (CPO) biodiesel is that it has high pour point which causes disadvantages in it™s use. North Sumatra is the second largest rubber producer in Indonesia, the use of rubber seeds as a bioadditive to reduce the pour point of CPO biodiesel is one of the right steps. The synthesis of rubber seed oil bioadditives is carried out in two processes; esterification process and transesterification process. This research aims to reduce the pour point of CPO biodiesel by mixing it with bioadditive of rubber seed oil. This study evaluated the effect of composition to find the best combination of biodiesel ratios in the mixture. The research results show that the greater the proportion of bioadditive rubber seed oil, the lower the pour point of the mixed biodiesel. Biodiesel with a low pour point is obtained at 10oC from mixing CPO biodiesel with bioadditive rubber seed oil at a composition of 75:25 and the optimal pour point is -7oC. Performance testing is carried out to differentiate fuel properties and fuel performance. The results show that B15 fuel produces the best performance at a maximum engine speed of 3000 rpm. In this round, a maximum power of 1.5708 kW was obtained, the lowest specific fuel consumption was 517.52 gr/kWh, thermal efficiency was 18.77%; the smallest CO content was 2.808%; HC 185 rpm; CO2 5.28%; NOx 4 ppm.